A General Fixed Point Theorem for Multivalued Mappings That Are Not Necessarily Contractions and Applications - Abdul Latif; Dinh The Luc (Abstract and Applied Analysis)
We prove a general theorem on fixed points of multivalued mappings that are not necessarily contractions and derive a number of recent contributions on this topic for contraction mappings.